Impact of digitalisation on the structure of youth political leadership - O. A. Sudorgin; A. V. Agafonov (Управление)
At the present stage, youth political leadership is in the focus of attention of researchers due to the fact that youth policy is an important part of public policy. The concept of the youth political leadership is relatively new and interdisciplinary, integrating politological, sociological, psychopolitical, and managerial approaches. To analyse the phenomenon, the systematisation of scientific approaches to the study of political leadership is conducted, 6 stages of the development of scientific thought from the second half of the XIX century to the beginning of the XXI one are highlighted. The classical and modern theories of leadership are considered. The article substantiates the mediation of methodological approaches to the political leadership by the historical and political context and the level of development of the political culture of society. They are the basis for studying the structure of the phenomenon in question. It is proved that under the influence of digitalisation as the most important aspect of reality, as an attribute of politics and the socio-economic sphere, the structure of the youth political leadership is undergoing a change. Digitalisation makes adjustments to the existing scientific and methodological basis of the political leadership. The analysis of available leadership concepts has shown a movement from its personal aspect to the socio-interactive one, however, in the context of digital transformation, it is necessary to introduce a digital component of leadership. Based on empirical data, the modern structure of the youth political leadership is derived, consisting of three components: personal, socio-interactive, and digital.